Taboo Words in the TV Series Stranger Things - Theresia Ria Anjani Kurniawati; Tofan Dwi Hardjanto (Lexicon, 2019)
This study investigates taboo words produced by teenagers in the TV series entitled Stranger Things Season 2. It classifies taboo words into five referents, that is, mental, physical, religious, scatological, and sexual terms, and also categorizes them based on their functions. The data were taken from the subtitles of this TV series. The results show that the most frequently used taboo words are related to scatological terms with 55 (43%) occurrences. However, the teenage characters in the TV series rarely uttered taboo words which refer to mental and physical terms. Taboo words in the TV series were used for two main purposes, swearing and insulting. Swearing serves as a means to only relieve emotions, while insults are uttered to verbally attack the interlocutors. The findings suggest that the teenage characters use taboo words mostly for expressing their emotions rather than causing harm on their interlocutors.